Upaya Meningkatkan Pendidikan Dalam Baca, Tulis Dan Mengenal Al-Qur`An Dengan Metode Iqro Pada Anak Usia Dini Di Yayasan Almawaddah - Sophiana, Astina Ria; Zailani, Zailani (Universitas Muhammadiyah Sumatera Utara, 2021)
The research aims to know how to read and write the application of Al quran with iqro methods in early childhood and the factors that support and impede learning to read and write the Qur`an. This research is a qualitative descriptive which examines data quality (concepts, thoughts and actions) and describe what it is. The result of learning to read and write firs penelitian Al quran with methods iqro prepared in a pkanned and systematic based on the curriculum RA. Secondly, there is a supporting factor in the application of methods iqro is the availability of books, media, and other learning tools that support this learning process. Theirn infrastructure and tenacity educators in the implementation of learning. While the inhibiting factors such as lack of training on a regular basis of the application of methods for Teachers Iqro RA. Still their parents are less attentive to the children in learning Al-QuranUpaya Meningkatkan Pendidikan Dalam Baca, Tulis Dan Mengenal Al-Qur`An Dengan Metode Iqro Pada Anak Usia Dini Di Yayasan Almawaddah